2005
DOI: 10.1086/432648
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Heterogeneity at the Serotonin Transporter Locus (SLC6A4) Confers Susceptibility to Autism and Rigid-Compulsive Behaviors

Abstract: Autism is a spectrum of neurodevelopmental disorders with a primarily genetic etiology exhibiting deficits in (1) development of language and (2) social relationships and (3) patterns of repetitive, restricted behaviors or interests and resistance to change. Elevated platelet serotonin (5-HT) in 20%-25% of cases and efficacy of selective 5-HT reuptake inhibitors (SSRIs) in treating anxiety, depression, and repetitive behaviors points to the 5-HT transporter (5-HTT; SERT) as a strong candidate gene. Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
349
2
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(371 citation statements)
references
References 75 publications
(92 reference statements)
17
349
2
3
Order By: Relevance
“…The most common assessed variants are a deletion/ insertion polymorphism in the transcriptional control region of the SLC6A4 gene with functional effects (5HTTLPR) [227][228][229] and a variable number of tandem repeat in intron 2 (STin2). Several studies have found an association of the short alleles of 5HTTLPR with AD, 217,[230][231][232][233] fewer studies of the long alleles. 234,235 Some studies did not replicate these findings.…”
Section: Chromosome 17mentioning
confidence: 99%
“…The most common assessed variants are a deletion/ insertion polymorphism in the transcriptional control region of the SLC6A4 gene with functional effects (5HTTLPR) [227][228][229] and a variable number of tandem repeat in intron 2 (STin2). Several studies have found an association of the short alleles of 5HTTLPR with AD, 217,[230][231][232][233] fewer studies of the long alleles. 234,235 Some studies did not replicate these findings.…”
Section: Chromosome 17mentioning
confidence: 99%
“…1,2 Here, we investigated these gene variants in obsessivecompulsive disorder (OCD), based on high degrees of TS/OCD comorbidity, plus G56A functionally resembling SLC6A4 I425 V in producing transporter gain-offunction. [2][3][4] SLITRK1 was uncovered as a candidate for TS owing to its < 230 kb proximity to a breakpoint of a 13q chromosomal inversion found in a child with TS and attention-deficit/hyperactivity disorder (ADHD), in addition to its role in neurite outgrowth.…”
mentioning
confidence: 99%
“…1,2 Here, we investigated these gene variants in obsessivecompulsive disorder (OCD), based on high degrees of TS/OCD comorbidity, plus G56A functionally resembling SLC6A4 I425 V in producing transporter gain-offunction. [2][3][4] SLITRK1 was uncovered as a candidate for TS owing to its < 230 kb proximity to a breakpoint of a 13q chromosomal inversion found in a child with TS and attention-deficit/hyperactivity disorder (ADHD), in addition to its role in neurite outgrowth. 1 Furthermore, screening of 174 additional TS probands for SLITRK1 variants revealed a truncating frameshift mutation, varCDfs, with complete loss of function in one, and a microRNA domain-affecting variant, var321, which leads to reduced reporter gene activity in vitro, in two other of these probands (Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations